Investigating the Land Subsidence Rate in Tous, Mashhad Plain, Using the DInSAR Technique - roghayeh delaram; samad fotohi; mohsen hamidianpoor; morteza salari (تحقیقات کاربردی علوم جغرافیایی)
The subsidence phenomenon is considered one of the most frequent hazards occurring worldwide and imposing irreparable damages every year. This phenomenon affects the ground’s surface and its layers and causes the ground deformation. It can be referred to as a morphological phenomenon that is associated with the gradual sinking of the ground and the vertical movement of materials. Among the various methods used to study the land subsidence pattern, the Differential Interferometric Synthetic Aperture Radar (DInSAR) technique has provided more accurate results. Therefore, this technique was used to investigate the subsidence rate in Mashhad plain from 2003 to 2010 and the Envisat ASAR (C-band) and Sentinel-1 ASAR (C-band) satellite images were employed during the year 2019. The results show that the highest subsidence rate of about 44 cm occurred in Qasem Abad and Kalateh-ye Barfi lands from 2008 to 2010. A subsidence rate of about 37 cm was also observed in the same area from 2007 to 2009. The interpolation results using piezometer well statistics show a decrease in groundwater levels in this area and confirm the accuracy of the results.